EFEK LINGKUNGAN KERJA DAN EFIKASI DIRI PADA KINERJA KARYAWAN - Ulfa Sofiatun; Anwar Mansyur (Universitas Ahmad Dahlan, 2021)
This study aims to examine the effect of work environment and self-efficacy on employee performance. The object of this research is a historical and tourism site in the Semarang City, namely the Sam Poo Kong Temple and Lawang Sewu. The research was conducted in quantitative method by distributing questionnaire to the employee in the both locations. The sampling method that purposive sampling technique with the criteria of respondents are employee has been working for at least one year. Based on the data collection, a sample of 107 employees was obtained to be analyzed. The data were analyzed using regression analysis method. The results of the study strengthen the findings of previous studies that work environment and self-efficacy have a positive effect on employee performance.